(untitled) (Experimental biology, 2018)
The work is devoted to the study of the relationship of breast cancer with the metabolic syndrome and genes involved in the metabolism of lipids. In the framework of this study, we recruited 136 participants diagnosed with breast cancer and 83 conditionally healthy participants in the control group. Among the diseases associated with breast cancer, hypertension, chronic bronchitis, ischemic heart disease, uterine myoma, cholecystitis, varicose veins of the lower extremities, pancreatitis are prevalent. The incidence of type 2 diabetes was 13.2%. Biochemical analysis on 18 metabolic parameters showed that in the group of patients compared with the control group, the level of homocysteine and vitamin B12 is much higher than normal. Data analysis showed a high correlation between homocysteine levels and the risk of developing breast cancer (OR = 15.29, CI = 5.67-41.28, p <0.001) in the study group. In the study of the association of polymorphisms of the investigated genes with the risk of developing breast cancer among women in Kazakhstan, the contribution of the association of polymorphisms of the studied genes with the risk of developing breast cancer among women in Kazakhstan revealed a protective effect in the genes FTO, PRKAA2 and STK11. In the case of the CRTC2 gene, an association with the risk of developing breast cancer was identified in an over-dominant model (OR = 1.95, CI = 1.1-3.46, p = 0.021). When studying the relationship between the genetic profile and metabolic parameters, it was found that the genotype of the C/C (wild) gene PRKAA2 can affect the increase in cholesterol at normal vitamin B12 values ​​(OR = 3.43, CI = 1.25-9.39: p <0.015) and the T / C genotype affect the increase in cholesterol at elevated vitamin B12 values ​​(OR = 3.23, CI = 1.1-9.52: p <0.035). From the analysis it follows that the level of homocysteine ​​can be used as a biomarker, which is part of the complex of diagnostic measures for breast cancer. In addition, the genotypes of the C / C and T / C of the PRKAA2 gene can be used as markers of cholesterol and vitamin B12 levels in the body. To study the association of other genes with biochemical indicators and the risk of developing breast cancer, an increase in the sample is necessary. Key words: breast cancer, metabolic syndrome, genetic profile.